Coping with urban waste problems in the Global South: An exploration towards circular economy - Maria Tomai; George Papachristos (University of Athens, Department of Economics, International Economics and Development Laboratory (IEDL), 2025)
The performance of waste management systems in cities has to improve to cope with rapid urbanisation and population growth trends. It is, therefore, necessary to develop a more in-depth understanding of how potential interventions may impact and improve the performance of waste management systems. This is particularly the case for countries in the Global South, in their pursuit of further progress towards sustainable development. This paper develops a system dynamics model to evaluate interventions in the solid waste management system of Accra, where rapid urbanisation and population growth will place its waste management system under increasing strain over the next decades. The model is used to evaluate interventions as to whether they can increase circular waste flows, reduce disposal to landfills and, thus, improve system performance in upstream source separation, midstream waste collection, and downstream waste treatment. The findings reveal that the government's planned expansion of waste recovery capacity in Accra addresses only part of the challenge and will be inadequate to manage the city's accelerating waste generation. The simulation results underscore the necessity of adopting an integrated approach to improve system performance and achieve progress toward sustainability goals. This involves educational interventions for raising awareness and infrastructural interventions across the whole value chain. This analysis improves our understanding of the critical bottlenecks and synergistic effects of upstream, mid-stream and downstream interventions. It also supports policy and decision-making by drawing attention to the delays and potential negative trade-offs involved between interventions.
Keywords: Q53; O13; Q01; C61; R11; 330; Waste management system; System dynamics modelling; Circular economy; Global South